If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X * 2 + x * 2 = -14 + -3 Reorder the terms for easier multiplication: 2X + x * 2 = -14 + -3 Reorder the terms for easier multiplication: 2X + 2x = -14 + -3 Combine like terms: -14 + -3 = -17 2X + 2x = -17 Solving 2X + 2x = -17 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2x' to each side of the equation. 2X + 2x + -2x = -17 + -2x Combine like terms: 2x + -2x = 0 2X + 0 = -17 + -2x 2X = -17 + -2x Divide each side by '2'. X = -8.5 + -1x Simplifying X = -8.5 + -1x
| -200x-2500=5100 | | -124=-4v-2(6+6v) | | -4x-18=73 | | y=x/2-13^3 | | 5-w+11=51 | | 7+7(7n-8)=98 | | 6x-(3x+7)=27 | | 2x+29=300 | | 6n^2+48n+72=0 | | 28n^2=-96-183n | | 5a+56=(7)(8) | | 10x^2y= | | n(3)=n+12 | | 3x+4x=16-3x | | 4c/5=4 | | 3x^2+8x^2-15x-40=0 | | 6(x+5)-42=8 | | 33xy^5z^3= | | h=16t^2+400t | | 8(x+2)=(6x-7) | | sinx+cosx=6x | | 15(x+1)-5(10x+9)+2(5x+3)+4=0 | | 7z-9=3 | | 4/3=10/x | | -4p=44 | | 11-a=13 | | 2x+14=-28 | | 6(-6x+4)=-8(4x-6) | | -x-13+25=-3+52 | | 75x-2=-14 | | (12x+1)=(20x+19) | | 5(r-8)-4(6r-4)=-8r-8r |